Synthesis, molecular dynamics simulation and adsorption study of different pollutants on functionalized mesosilica - Rasool Pelalak; Roozbeh Soltani; Zahra Heidari; Rahime Eshaghi Malekshah; Mohammadreza Aallaei; Azam Marjani; Mashallah Rezakazemi; Saeed Shirazian (Scientific Reports, 2021)
Abstract Experimental and computational works were carried out on a new type of mesoporous silica. In the experimental section, functionalized hollow mesosilica spheres were prepared via a facile technique and then evaluated using some analytical techniques (FESEM, TEM, L-XRD, FTIR, BET-BJH, and TGA). The obtained results revealed that the synthesized material had hollow structure with a diamino-grafted porous shell. The molecular separation of crystal Violet (CV) and neutral Red (NR) dyes from water were investigated by adsorption process using the synthesized powder. Influence of adsorbent loading was evaluated as adsorption ability and dyes removal efficiency. Also, the obtained modeling results revealed appropriate fitting of data with non-linear Langmuir model. The theoretical studies were employed to study the adsorption and removal mechanism of cationic (CV and NR) and anionic (orange II (OII)) dyes using molecular dynamics calculations. Moreover, the simulation outcomes provided valuable information about quantum chemical properties including the HOMO–LUMO maps, chemical reactivity, global softness (σ) and hardness (η) for silica-linker-water-dyes components.